Auriculotherapy: contributions to a group of smokers (Research, Society and Development, 2023)
Tobacco is the leading preventable cause of death and illness in the world. Considering that many people abandon tobacco cessation treatment, auriculotherapy is one of the possible complementary treatments for smoking. Aiming to identify contributions of auriculotherapy to a smoking group, from the perspective of the user and the auriculotherapy professional This is a descriptive study, with a qualitative approach with a smoking group organized by the municipal health department of a municipality in the interior of the state of Rio Grande do Sul. Data collection was carried out through semi-structured interviews, using a form as a guide carried out in the second half of 2022 with participants in the smoking group, being users and working professionals. Data analysis was carried out through content analysis of the speeches. It can be considered that auriculotherapy was well accepted in the participating group and its use as a complementary therapy suggests a decrease in anxiety, improvement in sleep quality, a feeling of calm and tranquility for people undergoing treatment for smoking.